Pengaruh Promosi Terhadap Keputusan Pembelian Yang Di Mediasi Oleh Minat Beli Konsumen Roxy Swalayan Ende - Roswita Meme; Rafael Octavianus Byre (ANALISIS, 2020)
This study aims to determine the effect of Promotion on:1) Customer Purchase Decisions  at Roxy Swalayan Ende, 2) Purchasing Intention at Roxy Swalayan Ende, 3)Buying Interest on Customer Purchasing Decisions at Roxy Swalayan Ende, and 4)Promotion on Customer Decisions mediated by Buying Interest at Roxy Swalayan Ende. This research includes causality research using a quantitative approach. the samples in this study were customers who shop at Roxy Swalayan Ende amounting to 50 people. Data collection used a questionnaire while data analysis performed using Path Analysis. The data were collected using questionnaires that have been tested for validity and reliability. Path analysis was used to test the hypothesis of this study. The results of this study indicate that: 1)promotion has positive and significance influence on Customer Purchase Decisions with a beta Value of 0,469, 2) promotion has positive and significant effect on purchase intention at Roxy Swalayan with beta value of 0,582, 3)purchase intention has positive and significant influence on Customer purchasing decisions at Roxy Swalayan Ende with beta value of 0,438, 4) promotion has positive and significant effect on customer purchasing decisions mediated by buying interest has a beta value of 0,254